Alfalfa hay induced primary photosensitization in horses. (May 2016) - Puschner, B.; Chen, X.; Read, D.; Affolter, V.K.
Highlights: Alfalfa hay can cause primary photosensitization in horses. Chlorophyll a, chlorophyll b, and pheophorbide a are not the causative photodynamic compounds. Growing and climate conditions resulting in the presence of photodynamic compounds in alfalfa hay are unknown. Abstract: Photosensitization, also known as photodermatitis, occurs when phototoxic or photoactive substances accumulate in the skin and interact with sunlight to result in an often severe, crusting, itching or painful dermatitis in unpigmented and/or lightly haired areas of the skin. Primary photosensitization, caused by direct ingestion of photosensitizing agents, has been reported anecdotally in horses after ingestion of alfalfa hay. Between 2004 and 2014, several large outbreaks of primary photosensitization in horses fed primarily alfalfa hay were investigated in California. Alfalfa hay samples were collected and carefully examined for the presence of known photosensitizing plants and pesticide residues but none were identified. Select hay samples were evaluated for unusual fungal infestation and for phototoxicity assay using a specific Candida albicans assay; results were negative. In the 2004 outbreak, a feeding study was conducted with three horses exclusively fed alfalfa hay that was suspected to have caused the outbreak. Two weeks after ingestion of alfalfa hay, two horses developed several lesions in non-pigmented skin characterized as chronic ulcerative and necrotizing dermatitis with superficial vasculitis, which was consistent with photosensitization. In the 2014 outbreak, seven different implicated alfalfa hay samples were analyzed for chlorophyll a and b, and pheophorbide a. These compounds had been suspected to play a role in alfalfa-induced primary photosensitization. The chlorophyll contents ranged from 0.90 to 2.30 mg/g in the alfalfa hay samples, compared to 1.37 and 2.94 mg/g in locally grown alfalfa and orchard grass hay. The pheophorbide a levels ranged from 3.36 to 89.87 µg/g in alfalfa samples compared to 81.39 and 42.33 µg/g in control alfalfa and orchard grass hay samples. These findings eliminate chlorophyll a, chlorophyll b, and pheophorbide a as possible causes for alfalfa-hay induced primary photosensitization.